2021
DOI: 10.1186/s12905-021-01172-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the status of marital burnout and related factors in married women referred to health centers

Abstract: Background Marital burnout is an important issue in marriage and many factors play an important role in this phenomenon. The aim of this study was to determine the status of marital burnout and the factors affecting married women who were referred to health centers because of it. Methods In this study, 936 women were selected by multistage sampling and data collection was performed using questionnaires of demographic and couple burnout. Data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Likewise, married HCWs had experienced significantly high levels of OB while it was not so in other research [ 15 , 30 ]. As married people had to play different roles, including responsibilities at home and childcare, they might have been subjected to higher burnout [ 53 ]. In the present study, having no children was significantly correlated with a higher prevalence rate of OB, in agreement with the survey by Jalili et al [ 30 ], but contrasting the reports by Huang et al and Lai et al [ 54 , 55 ] Childless people might also live through more depression and mental health problems [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, married HCWs had experienced significantly high levels of OB while it was not so in other research [ 15 , 30 ]. As married people had to play different roles, including responsibilities at home and childcare, they might have been subjected to higher burnout [ 53 ]. In the present study, having no children was significantly correlated with a higher prevalence rate of OB, in agreement with the survey by Jalili et al [ 30 ], but contrasting the reports by Huang et al and Lai et al [ 54 , 55 ] Childless people might also live through more depression and mental health problems [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study consisted of a descriptive study and a quasiexperimental study. A descriptive study was conducted to determine the marital burnout status of 936 married women at the Gonabad Health Center in Iran [25]. In the second stage, a quasi-experimental study was conducted on women with high rates of marital burnout to determine the impact of effective communication skills training on marital burnout among married women in Gonabad, Iran in 2020.…”
Section: Methodsmentioning
confidence: 99%
“…In previous study, it was found that there was a significant relationship between the number of children and somatic burnout; those who had more children reported higher levels of somatic burnout (Nejatian, et al, 2021). An increase in the number of children of some married couples increased their conflict rate and their quality of marriage decreased (Bulgan, 2018).…”
Section: An Overview Of Potential Worker Burnouts In Unitri Staff Dur...mentioning
confidence: 95%